Sequence analysis of ribosomal protein gene of ‘Candidatus Liberibacter asiaticus’ infecting major citrus cultivars in western Maharashtra of India - PRAMOD W. RAMTEKE; DILIP GHOSH*, SUMIT BHOSE, PRAGATI MISRA (Indian Phytopathology, 2015)
Citrus greening (Huanglongbing, HLB) is the most serious and destructive citrus disease known worldwide. It is caused by three different species of ‘Candidatus Liberibacter’, a Gram negative alpha-proteobacterium and classified on the basis of its geographical origins and 16Sr DNA sequence. During a survey conducted in the year 2010 in Maharashtra state of India, disease occurrence was recorded in different citrus species viz. sweet orange cv ‘Mosambi’, Rangpur lime, Nagpur mandarin, acid lime and rough lemon. The disease was found most prevalent in ‘Mosambi’ sweet orange cultivar and maximum disease incidence up to 41.5% was recorded in Ahmednagar district. Four different citrus species viz. sweet orange cv ‘Mosambi’, Rangpur lime, Cleopatra mandarin and acid lime showed variable symptoms of suspected greening disease in the field and were found positive for ‘Candidatus Liberibacter spp.’ through biological indexing and PCR assays using 16S rDNA primers. PCR amplifications and sequence comparison of another well conserved region, βoperon’s subunits rplA-rplJ confirmed the associated pathogen as ‘Candidatus Liberibacter asiaticus’. The sequence analysis of greening isolates in this geographical region revealed that all isolates were closely related to ‘Candidatus Liberibacter asiaticus’. The analysis of Single Nucleotide Polymorphisms at β- operon ribosomal protein (β-rp SNP) confirmed that irrespective of their host, all isolates strictly belonged to genetic group of β-rp SNP lineage II.